1970
DOI: 10.1017/s0043174500034391
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Purple Nutsedge

Abstract: Purple nutsedge(Cyperus rotundus L.)develops as a series of shoots connected by bulbs, rhizomes, and tubers. The leaves contain parallel, collateral vascular bundles with the majority of the photosynthetic cells concentrated in the sheathing girdle around each bundle. The upper leaf surface consists of a single layer of large epidermal cells covered by a thick cuticle. Stomates occur only in the lower surface. The vascular bundles vary from collateral to amphivasal as they pass from the leaves through the bulb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 11 publications
1
50
0
Order By: Relevance
“…3). Moreover, Wills & Briscoe (1970) have shown that the vascular rhizome system of C rotundus remained intact long after the aerial parts deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…3). Moreover, Wills & Briscoe (1970) have shown that the vascular rhizome system of C rotundus remained intact long after the aerial parts deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…Tuber age affects tuber dormancy. Neeser et al (1997) used the definition of Wills and Briscoe (1970) of primary dormancy as those tubers with no apparent sign of rhizome growth or with wiry, lignified rhizomes, and secondary dormancy as those tubers having previously sprouted that showed remains of lignified rhizomes attached to dormant tubers. With these definitions, Neeser et al (1997) reported that the dormancy of single tubers separated from the rhizome chains increased with cohort age, and that the increased tuber dormancy was primarily caused by the increase in secondary dormancy.…”
Section: Tuber Dormancy and Agementioning
confidence: 99%
“…Postemergence control of yellow nutsedge with chlorimuron and imazaquin was equivalent to, or better than, that with bentazon and glyphosate. Successful yellow nutsedge control with foliar-applied herbicides requires rapid absorption and translocation of the active ingredient to the meristematic cells of the basal bulb, rhizome apices, and tubers in sufficient quantities to kill the entire plant (Bhan et al, 1970;Hauser, 1963;Sprankle et al, 1975;Wills and Briscoe, 1970;Wills et al, 1980). Bentazon control of yellow nutsedge is often restricted due to the absence of basipetal translocation to parent tubers and very little acropetal translocation to other plant parts (Stoner et al, 1975).…”
mentioning
confidence: 99%